Legal Harmony: Integration of Customary, National, and Islamic Criminal Law in the Toraja Ma’rambu Langi - Islamul Haq; Resi Resi; Muhammad Suaib Tahir; Qurrah A’yuniyyah; Muh. Akram J Said (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
This research explores the integration of customary law, national law, and Islamic criminal law through a case study of ma’rambu langi in the Toraja community by firstly examining its effectiveness. Ma’rambu langi is a form of customary sanction imposed for severe moral violations, such as adultery and other breaches of local traditions. This sanction aims not merely to punish, but to restore social harmony through symbolic and public acts of moral responsibility. The offender is required to confess the wrongdoing and seek reconciliation with the community. The research adopts a qualitative method using semi-structured interviews with traditional leaders, community members, and legal practitioners, along with document analysis that includes customary case archives, court decisions, and relevant academic literature. The findings reveal that ma’rambu langi plays a significant role in maintaining social order, preventing the recurrence of offenses, and reinforcing the authority of customary law. Moreover, the study indicates that elements of this customary practice resonate with values in both national and Islamic criminal law, particularly in emphasizing restorative justice and communal integrity. The research contributes to ongoing discussions on legal pluralism in Indonesia, suggesting that harmonizing customary, national, and religious legal systems can enrich the development of a more inclusive, context-sensitive, and sustainable legal framework. It also emphasizes the importance of recognizing local wisdom in addressing moral and social issues while ensuring compatibility with broader legal principles and human rights norms.